Understanding the Cycle for Educational Inclusion in Ecuadorian Higher Education - Bell-Rodríguez, Rafael Félix (2020)
This paper aims to describe the different phases that make up the cycle for educational inclusion in higher education as a premise for the promotion of reflection and transformations that respond to the requirements for its establishment and proper functioning. In order to achieve the objective mentioned above, an investigation was conducted, following the general criteria of participatory action-research. As techniques for the collection of information, the interview was applied to eight students with disabilities and the survey, to 12 teachers; and the anecdotal record of the development of the workshops and sessions of training, in which 11 relatives of students with disabilities participated, was implemented. The description of the phases of transition / income, permanence with quality, effective discharge, titling, and monitoring has enabled the identification of the various factors, conditions and principles that have to be considered for the optimal functioning of a cycle. This cycle tries to provide a comprehensive vision and dynamics of the trajectory of students with disabilities in higher education. The trajectory has to be supported by the creation of conditions and the design of programs and services for educational inclusion, the application of different strategies aimed at fostering commitment, interest and the preparation of teaching staff, together with the recognition of the role of the family, as deduced from the main findings of the investigation.